Innovation of relational-communicative contexts for a transforming education - Crespo-Balderrama, Maritza (2021)
The research described here arose from the question of how to generate transformative processes in educational contexts, taking into account that, in Ecuador, education is still marked by the hierarchization of knowledge and relationships that seek homogenization and standardization. An innovative perspective was chosen for the process, social-relational constructionism, which looks at care and education as a creative, assertive, and proactive appropriation of everything that happens to us in life: links, work, relationships, and meaningful encounters; whose permanent learning processes need spaces for reflection and accompaniment. The relational research involved teachers, authorities, parents, and other members of educational contexts, over 4 years, and had as its scenario the implementation of the project "Caring for the Caregiver" for educational and protection institutions for children and adolescents in Tungurahua-Ecuador, between the years 2016 and 2019. The purpose of the research is to understand how from the collaborative-dialogical practices and the generative approach - as ways of being and doing - new relational conditions are created that put in the center the opening towards the diverse, the different and the local and in which the students build their own creative, emotional and relational resources. The result shows that freedom, dialogue, curiosity, critical reflection, respect for difference, and relational ethics enhance educational contexts and generate transformations that contribute to a life of dignity and to the construction of possibilities and common well-being.